Dehydrogenation Kinetics and Modeling Studies of MgH2 Enhanced by Transition Metal Oxide Catalysts Using Constant Pressure Thermodynamic Driving Forces - Saidi Temitope Sabitu; Andrew J. Goudy (Metals, 2012)
The influence of transition metal oxide catalysts (ZrO2, CeO2, Fe3O4 and Nb2O5) on the hydrogen desorption kinetics of MgH2 was investigated using constant pressure thermodynamic driving forces in which the ratio of the equilibrium plateau pressure (pm) to the opposing plateau (pop) was the same in all the reactions studied. The results showed Nb2O5 to be vastly superior to other catalysts for improving the thermodynamics and kinetics of MgH2. The modeling studies showed reaction at the phase boundary to be likely process controlling the reaction rates of all the systems studied.